Kurdish identity and image in Sunni and Shiite cultural sources Islamic Middle Ages - Mohammed, Dr. Yasin Taha (Sulaimani Journal for Humanities, 2025)
This research is aimed at analyzing Kurdish identity and their image in Islamic, Sunni and Shiite heritage sources, through the analysis of news and narratives that are based on text العصور الوسطى. It should be noted that the determination of Kurdish origins and their potential image in these sources is characterized by superstition and mystery, the result of interference between ethnic, religious and political factors, and dignity Text to accurate scientific methodology, thanks to its influence with imagination and myth. These sources are reflected in their collection of expressions of cultural hegemony, and rely on classifications based on the supreme view of Kurdish welfare, but lead to the frightening picture below They also point out that the Kurds themselves bear part of the responsibility in this context. The research of descriptive-analytical methodology relies on following the historical evolution of texts, with a focus on the similarities and differences between Sunni and Shiite images. Documentary to the Curriculum Comparison. It aims to discover the personal, political, religious and social factors that contribute to this negative image. The importance of this research is emphasized by providing an in-depth critical reading of Kurdish-related texts, and striving for a broader understanding of the issues and contexts involved in the format These pictures, taking into account the jurisprudence and Sharia criteria for Sunni and Shiite sects.
Keywords: Image of the Kurds; Kurdish identity; Sunni sources; Shiite sources; Islamic Middle Ages